The Effectiveness of Jigsaw Method in Learning Moral Creed at Al - Amri Integrated Islamic High School Probolinggo - Nur Kholila; Rahma El Yunusiah; Khadavi, Jadid (Kirana Publisher (KNPub), 2023)
The Jigsaw method applied to learning Aqidah Akhlak is an effective alternative method in improving students' understanding and social skills. This research involved students at the al-Amri Integrated Islamic High School as research subjects. This research aims to show the effectiveness of the Jigsaw method in learning Aqidah Akhlak at the Al-Amri Probolinggo Integrated Islamic High School. Data was collected through academic tests, observations and questionnaires. The results of this research confirm the effectiveness of the Jigsaw method in increasing students' understanding of Aqidah Akhlak. This helps teachers and schools in developing effective learning methods in the subject of Aqidah Akhlak. The Jigsaw method is very effective in improving students' social skills through the process of collaborating with other group members to understand and present material. In addition, the Jigsaw method can help students develop interpersonal communication skills